Psychological resources for academic buoyancy: the roles of growth mindset and emotional intelligence in Chinese university students - Liu, Ran (Frontiers in Psychology, 2025)
Background/introductionWhile psychological resources like growth mindset (belief in malleable abilities) and trait emotional intelligence (EI; self-perceived emotional capabilities) are individually important in higher education, their dynamic interplay with resilience (capacity to recover from adversity) in contributing to academic buoyancy (students’ ability to navigate daily academic challenges) warrants further understanding, particularly within the demanding context of Chinese university undergraduates and the specific mediating mechanisms involved.MethodsThis mixed-methods study employed a sequential explanatory design. The quantitative phase involved 381 undergraduates selected through stratified random sampling across several Chinese universities. Data were collected using established self-report instruments for growth mindset, trait EI, resilience, and academic buoyancy, and analyzed via structural equation modeling (SEM) to test a mediational model. The qualitative phase explored experiences of 20 purposefully selected students through reflective journals and a focus group, with data subjected to thematic analysis.ResultsQuantitative findings revealed that both growth mindset and trait EI significantly predicted resilience, which, in turn, significantly and positively predicted academic buoyancy. Resilience fully mediated the pathways from both growth mindset and trait EI to academic buoyancy. Multi-group analysis indicated no statistically significant gender differences in these pathways. Qualitative data richly contextualized these findings, illustrating how students practically apply growth mindset and emotional regulation to navigate academic setbacks and highlighting the crucial role of social support.Discussion/conclusionThese findings underscore that interventions targeting growth mindset and EI may foster resilience to enhance academic buoyancy in higher education. The results highlight the importance of these psychological resources, especially within demanding academic contexts, and suggest that fostering resilience is a key mechanism for improving students’ ability to manage routine academic stressors.